First record of Brachylaima (Trematoda: Brachylaimidae) in Salvator merianae (Squamata: Teiidae) - Fabiana Fedatto-Bernardon; Thainá Dutra-Vieira; Gertrud Müller (Revista Mexicana de Biodiversidad)
Twenty-four gastrointestinal tracts of Salvator merianae were examined for helminths research. Immature forms of Brachylaima sp. were identified with a prevalence of 4.16%. This is the first occurrence the Brachylaimidae for this host species in Brazil and in South America since the previous records of Brachylaima sp. in lizards were known only from Europe and Eurasia.